2023
DOI: 10.3389/fnhum.2022.1103872
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues of the central mechanism of two classic acupuncture manipulations based on fNIRS: suggestions for a pilot study

Abstract: Background: Acupuncture reinforcing-reducing manipulation (ARRM) is a necessary procedure of traditional Chinese acupuncture and an essential factor affecting the therapeutic effect of acupuncture. Shaoshanhuo reinforcing method (SSH) and Toutianliang reducing method (TTL) are the most representative ARRMs. They integrate six single ARRMs and pose distinguished therapeutic effects of acupuncture. However, due to the complexity, diversity, and variation, investigating the mechanism of these two classic manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The results revealed that different manipulations had different effects on inducing brain activation and altering the functional connectivity between the brain regions. Qu et al (2023) recruited healthy participants to receive the “Shaoshanhuo reinforcing” and “Toutianliang reducing” acupuncture manipulations at the left Quchi point at different times ( Qu et al, 2023 ). The results revealed that the Shaoshanhuo reinforcing method activated the bilateral primary MC and the left primary somatosensory cortex.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that different manipulations had different effects on inducing brain activation and altering the functional connectivity between the brain regions. Qu et al (2023) recruited healthy participants to receive the “Shaoshanhuo reinforcing” and “Toutianliang reducing” acupuncture manipulations at the left Quchi point at different times ( Qu et al, 2023 ). The results revealed that the Shaoshanhuo reinforcing method activated the bilateral primary MC and the left primary somatosensory cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, it has attracted increasing attention in the field of acupuncture treatment [86] . fNIRS is also utilized to investigate the central mechanism of acupuncture reinforcing-reducing manipulation, which has been shown to elicit notable cerebral responses [87] . Due to its noninvasive nature, portability, affordability, wearability, and minimal contraindications, fNIRS can be used continuously and repeatedly in both natural and clinical settings.…”
Section: A New Era In Acupuncture Therapy: Measuring Efficacy With Ev...mentioning
confidence: 99%